2006
DOI: 10.1515/cclm.2006.144
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac troponin T and amino-terminal pro-natriuretic peptide concentrations in fetuses in the second trimester and in healthy neonates

Abstract: We measured the concentrations of cardiac troponin T (cTnT) and amino-terminal pro-natriuretic peptide (NT-proBNP) in umbilical cord blood during the second trimester (20-25 weeks of gestation) and at delivery in 109 uncomplicated pregnancies to define reference values. Using the 97.5th percentile, the upper reference limits for cTnT and NT-proBNP were 0.308 ng/mL and 5402 pg/mL in fetuses in the second trimester, and 0.038 ng/mL and 1690 pg/mL in healthy neonates, respectively. We also evaluated whether labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 16 publications
3
33
0
3
Order By: Relevance
“…Additionally, cross reaction with fetal muscular troponin T cannot be excluded. The theory seems to be confirmed by studies conducted by Fortunato et al [9] in which cTnT concentrations in 22 healthy fetuses at 22-25 weeks of gestational age were comparable to concentrations found in preterm newborns born at 30 weeks of gestational age [9]. However, the studies performed by Clark et al [16] revealed that postnatal cTnT concentrations were usually higher than evaluated in cord blood.…”
Section: Discussionmentioning
confidence: 73%
“…Additionally, cross reaction with fetal muscular troponin T cannot be excluded. The theory seems to be confirmed by studies conducted by Fortunato et al [9] in which cTnT concentrations in 22 healthy fetuses at 22-25 weeks of gestational age were comparable to concentrations found in preterm newborns born at 30 weeks of gestational age [9]. However, the studies performed by Clark et al [16] revealed that postnatal cTnT concentrations were usually higher than evaluated in cord blood.…”
Section: Discussionmentioning
confidence: 73%
“…However, Fortunato et al reported that NT-proBNP was significantly higher in infants delivered by elective cesarean section than in infants delivered after spontaneous birth. In fact, NT-proBNP levels were higher after elective cesarean section than after a cesarean section carried out during active labor, suggesting that the decrease in NT-proBNP levels is probably attributable to labor rather than to the mode of delivery (19).…”
Section: Natriuretic Peptidesmentioning
confidence: 93%
“…BNP plays a major role in the organogenesis of the fetal heart and during the transition of newborn infants (NBIs) to extrauterine life. 3,4 In the first week of life, BNP levels are normally high, up to 12 times higher than maternal levels, since it does not cross the placental barrier. Such high value observed among healthy NBIs in the first days of life tends to return to normal with physiological loss in weight reaching a level similar to that observed in adults.…”
Section: Introductionmentioning
confidence: 99%